Propranolol inhibits angiogenesis via down-regulating the expression of vascular endothelial growth factor in hemangioma derived stem cell - Zhang, Ling (e-Century Publishing Corporation, 2013)
Background: Oral propranolol (PRN) has recently been shown to be highly effective for infantile hemangiomas (IHs), and is currently recommended as the first-line treatment of complicated IHs. However, the therapeutic mechanism(s) still remain unclear. Methods: In this study, we tested hemangioma-derived stem cells for expression of vascular endothelial growth factor (VEGF) in vitro and studied the inhibition of VEGF expression. We used PCR, Elisa, Western blotting and immunohistochemistry in vivo and in vitro trial. Results: The study demonstrated that application of PRN at a “normal” concentration equivalent to plasma concentration did not inhibit proliferation or promote apoptosis of hemangioma derived stem cells (HemSCs) isolated from IH patients. PRN suppressed expression of vascular endothelial growth factor (VEGF) and basic Fibroblast Growth Factor (bFGF) in HemSCs in vitro. Morphological, histological and immunohistological improvement were observed in vivo using murine IH model in which HemSCs pre-treated with PRN were implanted into BALB/c-nu mice. In the pre-treated HemSC grafts, mean micro-vessel density (MVD) significantly decreased and protein levels of VEGF markedly decreased, while bFGF was still detectable. Conclusions: The results suggested PRN inhibited angiogenesis via down-regulating the expression of vascular endothelial growth factor in hemangioma derived stem cell. These findings provide critical insight into the potential mechanisms of PRN action on IH.